Increasing Serum Levels of Nephronectin Based on Exposure Duration of Marble Dust in Industry Workers - Jimmy Akbar; Triwahju Astuti; Ngakan Putu Parsama Putra; Fitri Indah Sari (Jurnal Respirologi Indonesia, 2023)
Background: Exposure to silica dust is still an occupational health problem worldwide. The marble industry is one of the industries at risk of causing respiratory disease in its workers. Exposure to marble dust in the airways triggers pulmonary fibrosis via nephronectin (Npnt) as an α8β1 integrin ligand, which is an extracellular matrix protein. The purpose of this study is to look at how serum nephronectin (NPNT) levels change over time after being exposed to marble dust. Methods: This was a cross sectional analytical study of marble industry workers. A significant difference test is carried out on 4 groups of subjects (n=50), including marble industry workers with exposure durations of 1-5 years (n=12), 6-10 years (n=14) and >10 years (n=14), as well as non-marble industry workers (unexposed) as control subjects (n=10). A correlation test was performed to see the relationship between duration of exposure and serum Npnt levels.Results: The median age value in the exposed group was 40.5 (20-67) years. There was a significant difference (P=0.012) in the median Npnt level of the exposed group [1.699 (0.22–5.27) ng/mL] and the non-exposed group [0.678 (0.21–1.96) ng/mL]. The median value of nephronectin levels in the 10 years exposed group [2.4710 (1.74–5.27) ng/mL] were significantly different with both the 1–5 years exposed group (P=0.0001) with a median value of 0.6960 (0.22–2.27) ng /mL and the 6–10 years exposed group (P=0.039) with a median value of 1.0480 (0.27–4.29) ng/mL. There was a significant (P=0.0001) positive relationship (r=0.633) between the length of exposure and the level of Npnt. Conclusion: The duration of marble dust exposure had a significant effect on serum Npnt levels. The longer the marble industry workers were exposed to marble dust, the higher the serum Nephronectin level.